Implementasi Literasi Budaya Kuda Kosong dalam Meningkatkan Minat Membaca pada Mahasiswa Universitas Putra Indonesia - Librilianti Kurnia Yuki (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2020)
Abstract. Kuda Kosong culture is related to the history of the founding of Cianjur Regency, but there are still many Cianjur people who interpret that the Kuda Kosong is associated with something mystical or magical. This is caused by the low interest of the Cianjur community to read. In addition, there is still a lack of literacy related to the history of the Kuda Kosong. This study examines the implementation of the